The long-term cognitive consequences of adolescent exposure to recreational drugs of abuse - Mooney-Leber, Sean M. (Learn Mem, 2018)
During adolescence, the brain continues to undergo vital developmental processes. In turn, complex behavioral and cognitive skills emerge. Unfortunately, neurobiological development during adolescence can be influenced by environmental factors such as drug exposure. Engaging in drug use during adolescence has been a long-standing health concern, especially how it predicts or relates to drug using behavior later in life. However, recent findings suggest that other behavioral domains, such as learning and memory, are also vulnerable to adolescent drug use. Moreover, it is becoming increasingly apparent that deficits in learning and memory following adolescent drug use endure into adulthood, well after drug exposure has subsided. Although persistent effects suggest an interaction between drug exposure and ongoing development during adolescence, the exact acute and long-term consequences of adolescent drug exposure on substrates of learning and memory are not fully understood. Thus, this review will summarize human and animal findings on the enduring cognitive deficits due to adolescent drug exposure. Moreover, due to the fact that adolescents are more likely to consume drugs of abuse legally available to adults, this review will focus on alcohol, nicotine, and marijuana. Further, given the critical role of the frontal cortex and hippocampus in various learning and memory domains, the impact adolescent use of the previous listed drugs on the neurobiology within these regions will also be discussed.